The Discipline-Enhancing Role of Fiscal Institutions : Theory and Empirical Evidence - Debrun, Xavier (IMF Working Papers; Working Paper ;, 2007)
This paper discusses the role of fiscal institutions, including budget rules and non-partisan agencies, in enhancing fiscal discipline. A dynamic model of fiscal policy shows that optimal institutions lack credibility unless the costs to bypass them are sufficiently high. In our model, a combination of complete budgetary transparency and strong democratic accountability suffice to establish credibility. Under incomplete budgetary transparency, accountable governments may also use institutions as a signal of competence to increase their reelection chances, which in turn erodes the penchant for excessive deficits. In light of the theory, empirical tests of the effectiveness of institutions are undertaken. The results further emphasize that analysis should pay due attention to simultaneity bias (because disciplined governments may be more likely to adopt strict institutions). Also, interactions among different fiscal institutions, and between the latter and key features of the political system need to be explored further.